PECULIARITIES OF GENERATION CYCLES IN THE SETTLEMENT DEVELOPMENT SEQUENCES - Filiak, M.S. (Global Prosperity, 2023)
The article explores the relationship between generation cycles, settlement development, and economic progress. The authors argue that the cycles of development have led to a shift in societal values, particularly after World War II, with the "upper class" creating a state for the benefit of the "baby boomers" and their descendants. This shift has resulted in significant technological progress, which has concentrated in urban areas, and has led to a mass movement forward. However, this movement has come at the cost of decreased natural resources and increased social inequality. The article also discusses the importance of balancing the "stability of development" with the need to allocate a portion of natural resources to scientific and technological progress. The authors suggest that finding the right balance will require the participation of each generation. Specifically, some generations are born during times of change and learn to use dynamic opportunities, while others are born during times of stability and slow predicted movement, which can lead to stagnation. The authors argue that each generation should have a chance for a better life than what is considered average, as well as the opportunity for sudden happiness. Overall, the author suggests that by understanding the relationship between generation cycles, settlement development, and economic progress, it is possible to create a society that balances technological progress with social and environmental responsibility. Achieving this balance will require an ongoing effort from each generation, but it offers the potential for a peaceful jump in prosperity and the realization of the "American Dream."